Understanding Natural Approach for Teaching Productive Skills - arjulayana Arjulayana; Zainal Rafli; Siti Ansoriyah (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
This study is appointed to report the English teacher’s understanding of teaching productive skills through Neuro-Linguistics Programming. Neuro-Linguistics Programming as one of the approach in teaching English as a foreign language, with focusing on the brain anatomy, and it can stimulate student’s creative thinking, language uses, and motivation. Productive skills are need to be fostered by the students in learning English as a foreign language, because writing, and speaking are the most essential language skills. This research is uses qualitative descriptive method, with triangulation model in doing validity and reliability data. There are some steps applied in this research; Planning, observation, interviews, giving questionnaire, and the last is data analysis. The researcher focuses on the English lecturers who have taught English more than 2 years as subjects of the research. 7 questions in close - ended answer (yes/no answer) are given and 5 questions in short answer interview are implemented to gain the data regarding to lecturer’s understanding in NLP concept for teaching productive skills. 23 English Lecturers both male and female are to be the subjects of the research. From the data analysis, the result shows that almost of English lecturers know the NLP approach in teaching language, and they always give brain storming as a part of NLP concepts.